ANALISIS SEKUEN NUKLEOTIDA FRAGMEN 12S RIBOSOMAL MITOKONDRIAL DEOKSIRIBONUKLEOTIDA (MT-12S RDNA) YANG BERASAL DARI DAGING BABI DAN SAPI - , IRHAMNA PUTRI RAHMAWATI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Pig and cattle are the livestock which being breeded for the meat production. Demand towards the needs of meat protein are increasing together with the growth of society. However, the high demand towards meat especially beef is imbalance with the increasing of the product. This leads to cases of forgery and pork adulteration which has a similar physical characteristic with beef. In this modern era, all information should be presented in detail. Study of molecular method and genetic analysis is one of the best way to present the detail information. This research aims to analyze the genome of pig and cattle that circulated among local communities using nucleotide sequence of 12S ribosomal mitochondrial DNA (mt-12S rDNA). Amplification of mt-12S rDNA fragment by PCR technique used the DNA isolation result as a template, forward and reverse primer of mt-12S rDNA fragment. The amplification produced 456 bp of amplicon. The amplicon then was sequenced using Sanger method. The result of mt-12S rDNA sequences were analyzed using BLAST and MEGA version 5.2.2. program and were compared to pig and cattle mt- 12S rDNA sequence from GenBank database. The analysis showed there were 51 sites of difference between pig and cattle nucleotide sequences. Based on genetic distance analysis, there was similiarity between pig and cattle in this research and pig and cattle from GenBank database. Based on phylogeny tree which was analyzed using neighbor-joining method with bootstrap 1000x, pig has close relative to Asian class and cattle has close relative to Bos taurus. This research also resulted genetic markers for the mt-12S rDNA fragment of pig and cattle.